A Comparative Study of Single-tooth and Multi-tooth Stator of 4S-8P Permanent Magnet FSM for Electric Bicycle Application - Jusoh, Laili Iwani; Sulaiman, Erwan; Omar, M. Fairoz; Soomro, Hassan Ali (International Journal of Engineering and Technology, 2018)
This paper present a comparative study of single-tooth and multi-tooth stator of 4S-8P permanent magnet Flux Switching Machine (FSM) for electric bicycle application. Detailed comparison of the performance characteristics of the machines are presented that include important issues such as average torque, volume of PM, back-EMF and speed performance. For a fair comparison, the valid stator slot and rotor combinations is same dimension and analyzed using finite element analysis, and the one among of the design has the best electromagnetic performance is selected. On the basis of the investigation, it can be concluded that the single-tooth design of proposed permanent magnet FSM for a single phase 4S-8P topology has presented higher torque performance compared to multi-tooth design. However, since design of single-tooth exhibits a higher back-EMF, Design optimization and improvement structural is ongoing to achieve the best performance.